Morphological and Molecular Characterization of a New Isospora (Apicomplexa: Eimeriidae) Species From a Singing Honeyeater (Gavicalis virescens Vieillot, 1817) (Passeriformes: Meliphagidae) in Western Australia - Yinhua Chen; Belinda Brice; Bruno P. Berto; Rongchang Yang (Ecology and Evolution)
ABSTRACT We describe and characterize a new Isospora species from the Singing honeyeater (Gavicalis virescens) in Western Australia, both morphologically and molecularly. Microscopic analysis of a fecal sample identified 25 ellipsoidal oocysts, measuring 21–25 × 18–20 μm (mean 23.4 × 18.7 μm), with a length/width (L/W) ratio of 1.2–1.3 (mean 1.25). The oocyst wall is bilayered and ~1.0 μm thick, with a smooth outer layer making up about two‐thirds of the thickness. A micropyle cap, measuring ~2.0 × 4.5 μm, is present as a curved protrusion on the outer layer. The micropyle itself is ~4.5 μm wide. The oocysts lack a residuum but contain 1–2 polar granules. The 25 ellipsoidal sporocysts measured 14–15 × 8–9 μm (mean 14.1 × 8.7 μm) with an L/W ratio of 1.6–1.7 (mean 1.62). The Stieda body is flattened (~0.5 × 1.5 μm), the sub‐Stieda body is rounded (~1.5 × 2.5 μm), and the para‐Stieda body is absent. The sporocyst residuum, composed of clustered spherules, is ~3.5 × 3.5 μm. Sporozoites contain anterior and posterior refractile bodies and a nucleus. Molecular analysis of the 18S rRNA, 28S rRNA, and COI gene loci showed a 99.5% genetic similarity to Isospora neochmiae at the 18S rRNA locus and 99.2% and 97.7% similarities to Isospora manorinae at the 28S rRNA and COI loci, respectively. Phylogenetic analysis confirmed that the new species is closely related to I. manorinae. Based on these data, we propose this isolate as a new species, Isospora virescensae n. sp.